CD14 Mediates Binding of High Doses of LPS but Is Dispensable for TNF-α Production - Kinga Borzęcka; Agnieszka Płóciennikowska; Hanna Björkelund; Andrzej Sobota; Katarzyna Kwiatkowska (Mediators of Inflammation)
Activation of macrophages with lipopolysaccharide (LPS) involves a sequential engagement of serum LPS-binding protein (LBP), plasma membrane CD14, and TLR4/MD-2 signaling complex. We analyzed participation of CD14 in TNF-α production stimulated with 1–1000 ng/mL of smooth or rough LPS (sLPS or rLPS) and in sLPS binding to RAW264 and J744 cells. CD14 was indispensable for TNF-α generation induced by a low concentration, 1 ng/mL, of sLPS and rLPS. At higher doses of both LPS forms (100–1000 ng/mL), TNF-α release required CD14 to much lower extent. Among the two forms of LPS, rLPS-induced TNF-α production was less CD14-dependent and could proceed in the absence of serum as an LBP source. On the other hand, the involvement of CD14 was crucial for the binding of 1000 ng/mL of sLPS judging from an inhibitory effect of the anti-CD14 antibody. The binding of sLPS was also strongly inhibited by dextran sulfate, a competitive ligand of scavenger receptors (SR). In the presence of dextran sulfate, sLPS-induced production of TNF-α was upregulated about 1.6-fold. The data indicate that CD14 together with SR participates in the binding of high doses of sLPS. However, CD14 contribution to TNF-α production induced by high concentrations of sLPS and rLPS can be limited.